Deciphering the Intercellular Communication Between Immune Cells and Altered Vascular Smooth Muscle Cell Phenotypes in Aortic Aneurysm From Single-Cell Transcriptome Data - Cao, Genmao; Lu, Zhengchao; Gu, Ruiyuan; Xuan, Xuezhen; Zhang, Ruijing; Hu, Jie; Dong, Honglin (Frontiers in Cardiovascular Medicine, 2022)
Background: Vascular smooth muscle cell (VSMC) phenotype switching has been preliminarily found in aortic aneurysm. However, two major questions were raised: 1) What factors drive phenotypic switching of VSMC in aortic aneurysm? 2) What role does VSMC phenotype transformation play in aortic aneurysm? Method: We obtained single cell transcriptome data GSE155468 that incorporates 8 aortic aneurysm samples and 3 normal aorta samples. A standard single-cell analysis procedure was performed by Seurat (v3.1.2) for identifying the general cell components. Subsequently, VSMC were extracted separately and re-clustered for identifying switched VSMC phenotypes. Vital VSMC phenotypes were validated by immunofluorescence. Next, identified immune cells and annotated vital VSMC phenotypes were extracted for analyzing the intercellular communication. R package CellChat (v1.1.3) was used for investigating the communication strength, signaling pathways, and communication patterns between various VSMC phenotypes and immune cells. Result: Intercellular communication analysis was performed between immune cells (macrophages, B-cells, CD4+ T-cells, CD8+ T-cells) and immune related VSMC (macrophage-like VSMC, mesenchymal-like VSMC, T-cell-like VSMC, contractile VSMC). 27 signaling pathways with 61 ligand-receptor pairs were identified significantly among selected cell populations. Macrophages and macrophages-like VSMC both assume the roles of signaling sender and receiver, showing the highest communication capability. T-cells acted more as senders while B-cells act as receivers in the communication network. T-cell-like VSMC and Contractile VSMC are used as senders while mesenchymal-like VSMC play a poor role in the communication network. Signaling MIF, GALECTIN, and CXCL showed high information flow of intercellular communication, while signaling COMPLEMENT and CHEMERIN were completely turned on in aortic aneurysm. MIF and GALECTIN promoted VSMC switch into macrophage-like phenotype，CXCL, GALECTIN promoted VSMC transform into T-cell-like phenotype. MIF, GALECTIN, CXCL, COMPLEMENT, CHEMERIN all mediated the migration and recruitment of immune cells into aortic aneurysm. Conclusion: The sophisticated intercellular communication network existed between immune cells and immune related VSMC, and changed as aortic aneurysm progressed. Signaling MIF, GALECTIN, CXCL, CHEMERIN, and COMPLEMENT made a significant contribution to aortic aneurysm progression through activating immune cells and promoting immune cell migration, which could serve as the potential target for the treatment of aortic aneurysm.